PERILAKU CROSS HIJAB DI MEDIA SOSIAL TWITTER: (Analisis Perilaku Cross hijab sebagai Penyimpangan Seksual dalam Perspektif Ilmu Fikih) - Annisa Asyarofa; Faiza Hanin Nastiti (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2023)
Cross dressing is a sexual deviant behavior in which a man dresses like a woman and vice versa. Over time, the behavior of cross dressing in Indonesia has penetrated moslem clothing in general. Wearing headscarves, robes and veils they do as a form of moslem clothing cross dressing. A new designation has emerged for cross dressers dressed in moslem women, they are usually called cross hijabers. The spread of cross hijab on social media was marked by the discovery of several photos and videos of men wearing moslem’s clothing, such as headscarves, robes, and veils. Twitter is one of the social media used by cross hijabers to show their existence to the public. The discovery of several posts by cross hijabers wearing headscarves and robes currently circulating with various captions has proven this. The purpose of this research is to analyze and find cross hijab behavior on Twitter social media, cross hijab perspective according to jurisprudence, and factors that cause cross hijab behavior on Twitter social media. The approach in this study uses literature study by collecting data related to research from written sources and field studies through direct interviews with these actors and observers on Twitter social media. The results of the study show that: (1) The rise of cross hijab behavior on social media Twitter is marked by several posts and interactions between them. (2) The cross hijab issue has been regulated in fiqh with the prohibition to dress like the opposite sex. (3) There are several factors triggering cross hijab behavior, including: parenting mistakes, the influence of the surrounding environment, personal satisfaction, and dissatisfaction with oneself.